Digitization for Professional Training of Future Specialists in the Field of Vocational and Technical Education - Osadcha, Kateryna; Buksha, Mykhailo; Manzhula, Oleksandr (Educological discourse, 2023)
The article analyzes the problems of digitalization for professional training of future specialists in the field of vocational (vocational and technical) education, which arose in connection with the development and expansion of digital technologies and increased requirements for future specialists. On the basis of such scientific methods for research, analysis and systematization to scientific sources, modern results of digitalization of professional training of future specialists in the field of vocational (vocational and technical) education in Ukraine and abroad were studied. Prospective directions for further modernization of vocational (vocational and technical) education in Ukraine in the conditions of a digital society are outlined. First of all, it is appropriate to equip vocational (vocational and technical) education institutions with modern digital technology (computer classrooms with modern software, Internet communication and communication tools; open spaces and makerspaces for teachers and students, etc.). It is important that the administration of the vocational (vocational and technical) education institution should have a clear idea and strategy regarding the further use of expensive and modern equipment. The digital educational environment created on the basis of this should include technical, hardware, software and organizational structures that ensure the adjustment and functioning of the equipment and the operation to information services of the educational institution. In institutions and in the entire system of vocational (vocational and technical) education, the digital competence of pedagogical workers should be constantly monitored and methods of its improvement should be implemented in the system of professional development. In addition, it is necessary to use all means of the digital educational environment of the institution to vocational (vocational and technical) education for the formation and development of digital competence for future specialists in the field of vocational (vocational and technical) education (students).